Short Communication: Assessment of Pteridophytes’ composition and conservation status in sacred groves of Jhargram District, South West Bengal, India - Dr. Uday Kumar Sen Uday; RAM KUMAR BHAKAT (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Uday UKS, Bhakat RK.. 2021. Short Communication: Assessment of Pteridophytes’ composition and conservation status in sacred groves of Jhargram District, South West Bengal, India. Biodiversitas 22: 3171-3178. Sacred groves are significant as community-preserved areas and have contributed to the conservation of biodiversity, thereby playing a key role in environmental management. The ecological and related cultural values of the species and the activities of local communities would make it possible to understand the importance of the protection of the sacred groves and also to prepare integrated approaches to biodiversity at the ecosystem level. Thus, this study aimed to investigate the status of pteridophyte diversity in the sacred groves of Jhargram district, West Bengal, India. The study showed that 77 pteridophyte species belonging to 44 genera and 15 families were collected and described, of which nine species were classified as Lycopodiopsida and sixty-eight species as Polypodiopsida. The floristic analysis revealed the dominance of the order Polypodiales (70.13%) followed by Aspleniaceae (23.38%), and Polypodiaceae (23.38%). The results also showed the predominance of the genera Selaginella with five species. Of the total species, 76.62% were terrestrial species, 14.29% were epiphytes, and 9.09% were aquatic species. The highest frequency is shown by Class C (25.97%) and major pteridophyte plants (81.81%) were not been evaluated till now.